Diseases of the urinary system of cows: 2- Causative bacteria and Haematological changes. - Al-Samarrae,, S. A.G.; Al- Azawi, W. S.T. (The Iraqi Journal of Veterinary Medicine, 1999)
Urine samples for bacterial cultures (697) and (604) blood samples for packed cell volume, haemoglobin concentration total plasma protein , blood urea nitrogen and creatinine level were collected farms and veterinary clinics (control) and two cow stations in Al- Latifia and Al Dijala. The bacterial cultures revealed negative results in the control cows , while bacteria isolated from urine samples in the two stations were similar, and they were Staphylococcus aureus, Corynebacterium renale, haemolytic Escherchia coli . and Corynebacterium pyogenes ( 32, 35,15,8) in Al- Latifia station and (84,136,135,8) in Al-Dijala station respectively Blood examination showed that packed cell volume, haemoglobin concentration, and total plasma protein showed low levels in Al- Dijala , while blood urea nitrogen and creatinine level showed higher levels in the same coup of cows in comparision with the control and Al Latifia cows. Infectious pustular vulvovaginitis infected the reproductive system of all cows examined in the Al - Dijala station was behined the 100% bacterial isolate . The numbers of bacterial colonies in cultures from this ststion were more than ( 100000 ) coloni / cc. urine. The prevelance of urinary infection at the age of 3, 4,5,6,7years was 6.25% ; 16.47% , 25.71% , 27.77% and 20.75% respectively and the over all present of bacterial isolates in this study was 36.4%.